2016
DOI: 10.1002/pros.23192
|View full text |Cite
|
Sign up to set email alerts
|

Combining lymphovascular invasion with reactive stromal grade predicts prostate cancer mortality

Abstract: Evaluating LVI together with reactive stromal grade on diagnostic biopsies could be used to identify patients at high risk of death from prostate cancer. Prostate 76:1088-1094, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…32 The authors also published on the relationship between reactive stroma grading and perineural invasion 33 and lymphovascular invasion. 34 Like our results, a group from Brazil 35 found that stromogenic carcinoma predicts biochemical recurrence on univariate but not multivariate analysis (266 patients). Unfortunately, a GL7 subset was not included in their analysis.…”
Section: Validation Of Stromogenic Carcinomasupporting
confidence: 77%
“…32 The authors also published on the relationship between reactive stroma grading and perineural invasion 33 and lymphovascular invasion. 34 Like our results, a group from Brazil 35 found that stromogenic carcinoma predicts biochemical recurrence on univariate but not multivariate analysis (266 patients). Unfortunately, a GL7 subset was not included in their analysis.…”
Section: Validation Of Stromogenic Carcinomasupporting
confidence: 77%
“…CAFs secrete high levels of a number of factors, including TGF‐ß, EGF, FGF, hepatocyte growth factor, insulin‐like growth factor‐1, interleukin‐6, and C‐X‐C motif chemokine ligand 12 (stromal cell‐derived factor‐1) that might reasonably be expected to act in a paracrine fashion and potentially promote tumorigenesis 42,44,45 . Seminal work on PCa stromal grading showed that reactive stroma grading is an independent predictive factor for PCa biochemical recurrence and PCa‐specific death 46–50 . In addition, functional and phenotypic heterogeneity is characteristic of CAFs, even of those extracted from the same tissues 51 …”
Section: Tissue Recombination Modelsmentioning
confidence: 99%
“…Seminal work on prostate cancer stromal grading showed that the two groups of tumors that are most aggressive are, 1) those with almost no stromal involvement, these seem to be independent of their microenvironment from early in their pathogenesis; and, 2) tumors that exhibit an abundant stromogenic response, where the stroma appears to be a major contributor to tumor growth and invasion (Ayala et al, 2003). Reactive stroma grading (RSG) is an independent predictive factor for PCa biochemical recurrence and PCa specific death (Ayala et al, 2011, McKenney et al, 2016, Saeter et al, 2015, 2016, Yanagisawa et al, 2007). …”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 99%
“…Reactive stromal grading (RSG) is an independent system based upon stromal phenotypes to divide tumors into one of four reactive stromal grades (0–3) (Yanagisawa et al, 2007, 2008). RSG provides a predictive factor for biochemical recurrence and disease-specific death in prostate cancer patients (Saeter et al, 2015, 2016) and can add significant predictive value to Gleason grading (McKenney et al, 2016). In contrast to clonal somatic gene studies, many differences have been found in gene expression between CAF and normal fibroblasts.…”
Section: Genetic and Genomic Analysis Of Cancer-associated Fibroblastsmentioning
confidence: 99%